SOSIALISASI IMPLEMENTASI PROGRAM SANITASI TEMPAT TINGGAL BAGI PEKERJA MIGRAN INDONESIA DI JOHOR BAHRU, MALAYSIA - Setiakarnawijaya, Yasep Setiakarnawijaya; Samsi Setiadi; Kuswahyudi (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
ABSTRACT Indonesia Migrant Workers (IMW) in the Johor Bahru region of Malaysia as a community service partner, face problems related to the quality of sanitation in their residences due to the lack of knowledge, understanding, insight, and awareness of Indonesia's migrant workers. This problem of the quality of sanitation in residential areas has an impact on the quality of life of migrant workers in Johor Bahru, Malaysia. In order and efforts to increase the knowledge, insight, and awareness of Indonesia migrant workers in the Johor Bahru area regarding the quality of sanitation in their homes, this community service activity was carried out in collaboration with LPPM-ALPTKNI and in collaboration with one of the universities in Johor, namely Universiti Tun Hussein Onn Malaysia (UTHM). This activity will also support the efforts of the Indonesian Community Center (ICC) by the Indonesian Consulate General in Johor Bahru in the context of empowering Indonesia migrant workers in Malaysia. The methods used in the training are lectures, mentoring and providing assistance for ICC administrators. This service activity aims to: 1) increase IMW's knowledge, understanding, insight, and awareness regarding residential sanitation; 2) increasing behavioral understanding and awareness of the importance of maintaining a healthy environment for a better quality of life. The results of the service received appreciation from the Indonesian Consulate General in Johor Bahru and the ICC where the service was carried out. The Consulate General of the Republic of Indonesia and the ICC hope that the service activities that involving Indonesia Migrant Workers in Johor Bahru can be done in the following year. Keywords: Sanitation of Housing, Indonesia Migrant Workers, Quality of Life. ABSTRAK Pekerja Migran Indonesia (IMW) di wilayah Johor Bahru Malaysia sebagai mitra pengabdian masyarakat, menghadapi permasalahan terkait kualitas sanitasi tempat tinggal akibat kurangnya pengetahuan, pemahaman, wawasan, dan kesadaran pekerja migran Indonesia. Masalah kualitas sanitasi tempat tinggal ini berdampak pada kualitas hidup pekerja migran di Johor Bahru, Malaysia. Dalam rangka dan upaya meningkatkan pengetahuan, wawasan, dan kesadaran para pekerja migran Indonesia di wilayah Johor Bahru mengenai kualitas sanitasi tempat tinggal, dilakukan kegiatan pengabdian masyarakat ini dilaksanakan bekerja sama dengan LPPM-ALPTKNI dan bekerja sama dengan salah satu perguruan tinggi di Johor, yaitu Universiti Tun Hussein Onn Malaysia (UTHM). Kegiatan ini juga akan mendukung upaya Indonesian Community Center (ICC) oleh KJRI Johor Bahru dalam rangka pemberdayaan pekerja migran Indonesia di Malaysia. Metode yang digunakan dalam pelatihan adalah ceramah, pendampingan dan pemberian bantuan bagi pengurus ICC. Kegiatan pengabdian ini bertujuan untuk: 1) meningkatkan pengetahuan, pemahaman, wawasan, dan kesadaran IMW mengenai sanitasi tempat tinggal; 2) meningkatkan pemahaman perilaku dan kesadaran akan pentingnya menjaga lingkungan yang sehat demi kualitas hidup yang lebih baik. Hasil Pengabdian mendapat apresiasi dari KJRI Johor Bahru dan ICC tempat pengabdian dilaksanakan. Pihak KJRI dan ICC berharap agar kegiatan pengabdian yang melibatkan Pekerja Migran Migrant Indonesia di Johor Bahru dapat dilakukan pada tahun tahun berikutnya. Kata Kunci: Sanitasi Tempat tinggal, Pekerja Migran Indonesia, Kualitas hidup.